2000
DOI: 10.1063/1.126519
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic moment of Mn in the ferromagnetic semiconductor (Ga0.98Mn0.02)As

Abstract: We have studied the quasibinary ferromagnetic semiconductor (Ga0.98Mn0.02)As by magnetic circular dichroism in x-ray absorption. We find a richly structured Mn absorption spectrum typical for localized 3d electrons. An analysis of the magnetization-averaged and dichroism line shapes shows a local Mn moment of 4.6μB, which is close to the Hund’s rule moment for the half-filled 3d shell. The magnitude of the dichroism reveals that only about 1/7 of the Mn atoms participate in the ferromagnetic order. Our experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
79
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 13 publications
18
79
2
Order By: Relevance
“…The XAS/XMCD arising from Mn-1 has been associated to a mixed-valence ground state due to the large Mn 3d hybridization with the surrounding 4sp states. 19,24,25 Numerical calculations indicated a mixed 80% d 5 -20% d 6 L ground state ͑L is a ligand hole͒. 24,25 In Mn-AP, both the energy shift of the XMCD minimum and the line shape suggest a different valence state with lower occupancy of the 3d levels, implying a lowering of the d 6 character and increment of the d 5 one.…”
Section: Methodsmentioning
confidence: 99%
“…The XAS/XMCD arising from Mn-1 has been associated to a mixed-valence ground state due to the large Mn 3d hybridization with the surrounding 4sp states. 19,24,25 Numerical calculations indicated a mixed 80% d 5 -20% d 6 L ground state ͑L is a ligand hole͒. 24,25 In Mn-AP, both the energy shift of the XMCD minimum and the line shape suggest a different valence state with lower occupancy of the 3d levels, implying a lowering of the d 6 character and increment of the d 5 one.…”
Section: Methodsmentioning
confidence: 99%
“…Within this class of materials, the magnetic semiconductors are particularly challenging, not only because they can replace magnetic elements in storage media, but because they can be used as spin injectors into normal semiconductors [3,4] for completely novel applications. In the field of magnetic semiconductors a new chapter has been opened by the III-V diluted magnetic semiconductors (DMS), especially with (Ga, Mn)As.Experimentally (Ga, Mn)As can be manufactured using low-temperature molecular beam epitaxy (LT-MBE) [5,6,7,8] and its magnetic properties have been measured with numerous techniques [5,6,7,8,9,10,11]. (Ga,Mn)As is ferromagnetic (see e.g.…”
mentioning
confidence: 99%
“…Experimentally (Ga, Mn)As can be manufactured using low-temperature molecular beam epitaxy (LT-MBE) [5,6,7,8] and its magnetic properties have been measured with numerous techniques [5,6,7,8,9,10,11]. (Ga,Mn)As is ferromagnetic (see e.g.…”
mentioning
confidence: 99%
“…12 The contribution of magnetic and nonmagnetic 3d states to the x-ray absorption process can be separated by using the difference ͑XMCD͒ and sum ͑XAS͒ of spectra taken with opposite x-ray helicities. Although these techniques have been applied to ͑Ga 1−x Mn x ͒As previously, [13][14][15][16][17] the results are in some points inconsistent. The first experiments 13,14 found a pronounced multiplet structure in the Mn XAS spectra characteristic of a highly localized state.…”
Section: Introductionmentioning
confidence: 99%
“…Although these techniques have been applied to ͑Ga 1−x Mn x ͒As previously, [13][14][15][16][17] the results are in some points inconsistent. The first experiments 13,14 found a pronounced multiplet structure in the Mn XAS spectra characteristic of a highly localized state. The weak XMCD signal indicated that only a fraction of 13% of the Mn atoms participate in the longrange ferromagnetic ordering.…”
Section: Introductionmentioning
confidence: 99%